HUBUNGAN ANTARA PELAKSANAAN KERJA KOMITE AUDIT DENGAN TINGKAT PENGUNGKAPAN MODAL INTELEKTUAL - Agustin Leonita, Irma (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2019)
The purpose of this research was to describe duties and responsibilities of audit committee, intellectual capital (IC) disclosure level, and the relationship between duties and responsibilities of audit committee and IC disclosure level. This research used 8 samples of pharmaceutical companies listed in Indonesia Stock Exchange period 2010. Samples was collected by used saturated sample method. The measurement of independent and dependent variable were used content analysis method and the hypothesis tested by used rank spearman’s correlation (). This research indicated that 50% of 8 pharmaceutical companies, its audit committee had done more or less than 7 duties and responsibilities of audit committee indicators. 2 of 8 pharmaceutical companies, its audit committee had done 7 duties and responsibilities of audit committee indicators and audit committee for another 2 companies had done 8 duties and responsibilities of audit committee indicators. On dependent variable, the result of descriptive analysis show that 50% of 8 pharmaceutical companies disclosed IC more or less than 11.5 indicators of IC and 2 of 8 pharmaceutical companies disclosed 13 indicators of IC. The result of hypothesis testing indicated that there was a positive and significant relation between duties and responsibilities of audit committee and IC disclosure level on 10%’s alpha.